Fraudulent Financial Reporting Detection Model in the Technology Industry: Case Study in Indonesia - Gina Arasy Noer; Putri Viona Pansesti; Ida Rosnidah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Since technology companies' stock performance has skyrocketed during the pandemic, this study aims to determine if this surge in performance is a result of their lack “fraudulent financial of reporting. Examining the effects of pressure, opportunity, rationalisation, and ability—the four pillars of diamond fraud theory—on the identification of fraudulent financial-reporting is the primary goal of this research. There are four variables: financial stability (representing pressure), external auditor-quality (representing opportunity), total accruals to total assets (representing rationalisation), and ability (representing change of director). This study employs a method known as hypothesis testing to provide an explanation. This study uses a sample of 24 companies listed on the IDX as its primary data source for the years 2020 and 2022. Analysis of data by means of multiple linear regression. A person's capacity, opportunity, rationalisation, and pressure all play significant roles in the prevalence of fraudulent financial reporting, according to the” study. Together with other recent studies in the IT industry, this one helps bring down the prevalence of false financial reporting in that field.